Analysis of the Clinical Value of High-Frequency Ultrasound in Differentiating Orbital Lymphoma from Inflammatory Pseudotumor - Zhong, Hua; Li, Hua (Pacific International Journal, 2024)
This study aims to investigate the clinical value of high-frequency ultrasound in distinguishing between orbital lymphoma and inflammatory pseudotumor. The research questions include: Can high-frequency ultrasound provide sufficient information to differentiate these two lesions? What is its diagnostic accuracy? What are the advantages and limitations of high-frequency ultrasound compared to existing imaging techniques? By addressing these questions, we hope to offer clinicians a more effective and safer diagnostic tool to improve the diagnosis and treatment of patients with orbital lymphoma and inflammatory pseudotumor.